Editorial - Siegfried Nagel; Christoffer Klenk; Pascal Stegmann (Bern Open Publishing, 2023)
The vision of the University of Bern is "knowledge generates value". In the context of this guiding idea, Bernese Sport Science works as "problem-oriented Sport Science", taking sound methodical, theoretical, and interdisciplinary approaches to achieving impact across scientific and societal dimensions. The programme of the 2023 SGS conference sheds light on the following perspectives: • Sport science generates value: Sport science makes an important contribution to the generation and transfer of knowledge in organisations and institutions in physical education, health promotion, high-performance sport and mass sport. • Knowledge of sport generates value: The knowledge generated in research contributes to the further development of physical education, to the targeted promotion of health and physical activity, to ethically optimized performance in elite sport and to ways people actively spend their leisure time. • Sport generates value: The social value of sport has multi-layered effects, such as personal development, teaching norms and values, the promotion of physical performance and health, and contributing to integration and social cohesion. A look at the Book of Abstracts shows a rich and inspiring scientific programme with nearly 100 contributions of academics and practitioners generating knowledge along the three perspectives described. During the conference, there were three keynotes from outstanding experts in the field of sport science, the Young Investigator Award with five presentations of talented young researchers, twelve thematic symposia, eight oral sessions with forty presentations and two poster sessions with short presentations. Besides the scientific contributions, the conference served as network platform that enabled many opportunities for fruitful and vibrant discussions as well as to connect with colleagues and establish research networks. None of this would have been possible without our fantastic organising team, the significant support of the SGS, particularly its board and the scientific committee and the commitment of researchers and practitioners in Switzerland and beyond that contributed to the conference's success. Thank you very much to all! We hope you enjoy reading the contributions of the Book of Abstracts. For the local programme committee Siegfried Nagel, Christoffer Klenk & Pascal Stegmann